Holocaust and Genocide Studies (Oxford)
The major forum for scholarship on the Holocaust and other genocides, Holocaust and Genocide Studies is an international journal featuring research articles, interpretive essays, and book reviews in the social sciences and humanities. It is the principal publication to address the issue of how insights into the Holocaust apply to other genocides. Articles compel readers to confront many aspects of human behavior, to contemplate major moral issues, to consider the role of science and technology in human affairs, and to reconsider significant political and social factors.
Keywords: Holocaust and Genocide